Echocardiographic reference ranges for normal cardiac Doppler data in healthy Turkish population : ECHO-DOP-TR Trial - Şafak, Özgen; Gürsoy, Ozan; Emren, Volkan; Demir, Emre; Yıldırım, Tarık; Argan, Onur; Şimşek, Ersin Çağrı; Aytemiz, Fatih; Özdemir, Emre; Bayar, Nermin; Erkal, Zehra; Çelik, Oğuzhan; et al. (Wiley, 2020)
AbstractAimDoppler echocardiography has become the standard imaging modality for diastolic function and provides pathophysiological insight into systolic and diastolic heart failure. In this study, we aimed to obtain normal echocardiographic Doppler parameters of healthy Turkish population.MethodsAmong 31 collaborating institutions from all regions of Turkey, 1154 healthy volunteers were enrolled in this study. Predefined protocols were used for all participants during echocardiographic examination and The American Society of Echocardiography and European Association of Cardiovascular Imaging recommendations were used for echocardiographic Doppler measurements.ResultsA total of 967 healthy participants were enrolled in this study after applying exclusion criteria. Echocardiographic examination was obtained from all subjects following predefined protocols. Mitral E wave velocity and E/A ratio were higher in females and decreased progressively in advancing ages. E wave deceleration time and A wave velocity were increased with aging. Assessment of tissue Doppler velocities showed that left ventricular lateral e′, septal e′, and septal s′ were higher in younger subjects and in females. E/e′ ratio was increased progressively with advancing decades. Right ventricular e′ and s′ were decreased but a′ was increased with increasing age. Septal e′ lower than 8 cm/s was 1.9% in the fifth decade and 13.7% in ages older than 50 years. The E/e′ ratio greater than 15 (and also 13) was not found.ConclusionThis study, for the first time, provides echocardiographic reference ranges for normal cardiac Doppler data in healthy Turkish population which will be useful in routine clinical practice as well as in future clinical trials.
Keywords: Aged, 80 and over; Turkey; Diastolic Function; Systole; Aratio; diastolic function; E/A Ratio; tissue Doppler imaging; Tissue Doppler Imaging; Middle Aged; Pulsed-Wave Tissue Doppler; Doppler echocardiography; E; Doppler Echocardiography; E / A ratio; Diastole; Echocardiography; Reference Values; Pulsed-wave Tissue Doppler; Humans; Female; pulsed-wave tissue Doppler; Aged; 3. Good health